Experiments on the Fehrer-Raab effect and the 'Weather Station Model' of visual backward masking. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The Fehrer-Raab effect (simple reaction time is unaffected by metacontrast masking of the test stimulus) seems to imply that a stimulus can trigger a voluntary reaction without reaching a conscious representation. However, it is also possible that the mask triggers the reaction, and that the masked test stimulus causes a focussing of attention from which processing of the mask profits, thus reaching conscious representation earlier. This is predicted by the Weather Station Model of visual masking. Three experiments tested this explanation. Experiment 1 showed that the masked test stimulus caused a temporal shift of the mask. Experiment 2 showed that the reaction in the Fehrer-Raab effect was not exclusively triggered by a conscious representation of the test stimulus: the mask was involved in evoking the reaction. Experiment 3 again revealed a temporal shift of the mask. However, the shift was only about half as large as the Fehrer-Raab effect. The psychometric functions suggested tha
Keywords: Fehrer-Raab effect; Weather Station Model; visual backward masking; reaction time; metacontrast masking; conscious representation; Cognition; Humans; Perceptual Masking; Pilot Projects; Psychology; Experimental; Psychometrics; Reaction Time; Visual Perception; Models; Reaction Time; Visual Contrast; Visual Masking

Visual attention and the mechanism of metacontrast. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The U-shaped metacontrast function may result from the superimposition of two monotonic components which reflect the effects of mechanisms similar to the peripheral and central processes suggested for backward pattern masking by Turvey (Psychol Rev 80:1-52, 1973). In an experiment using the disc-ring paradigm, it was demonstrated that the decreasing and increasing branches of the metacontrast function are differently affected by the exposure duration of the mask and a task-irrelevant stimulus (distractor) appearing in the contralateral visual hemifield. The phenomenal representation of masking is different for the two parts of the curve. It is suggested that masking in the second part of the masking function, but not in the first, is related to the control of visual attention. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual attention; metacontrast; backward pattern masking; monotonic components superimposition; Attention; Contrast Sensitivity; Humans; Judgment; Perceptual Masking; Visual Perception; Metacognition; Visual Contrast; Visual Attention; Visual Masking

Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type. - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta Psychologica)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184-197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation w
Keywords: latency facilitation; temporal order judgments; visual processing; priming; conscious perception; visual mask; Adult; Attention; Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Space Perception; Time Perception; Visual Perception; Consciousness States; Judgment; Priming; Visual Masking; Temporal Order (Judgment)

Evidence against response bias in temporal order tasks with attention manipulation by masked primes. - Scharlau, Ingrid (Psychological Research)
Attending to a location shortens the perceptual latency of stimuli appearing at this location (perceptual latency priming). According to attentional explanations, perceptual latency priming relies on the speeded transfer of attended visual information into an internal model. However, doubts about the attentional origin have repeatedly been raised because efforts to minimize response bias have been insufficient in most studies. Five experiments investigated the contribution of a response bias to perceptual latency priming (judgment bias due to the two-alternative forced-choice method and due to the existence of the prime, criterion effects or second-order bias, sensorimotor priming). If any, only small response biases were found. The results thus support the attentional explanation. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: response bias; temporal order tasks; attention manipulation; masked primes; perceptual latency priming; Adult; Attention; Discrimination Learning; Female; Humans; Male; Memory; Short-Term; Orientation; Pattern Recognition; Visual; Perceptual Masking; Psychomotor Performance; Psychophysics; Reaction Time; Serial Learning; Attention; Latent Learning; Priming; Response Bias; Visual Perception; Response Latency; Temporal Order (Judgment)

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Temporal parameters and time course of perceptual latency priming. - Scharlau, Ingrid; Neumann, Odmar (Acta Psychologica)
Visual stimuli (primes) reduce the perceptual latency of a target appearing at the same location (perceptual latency priming, PLP). Three experiments assessed the time course of PLP by masked and, in Experiment 3, unmasked primes. Experiments 1 (N=11; mean age 26.9) and 2 (N=12; mean age 25.6) investigated the temporal parameters that determine the size of priming. Stimulus onset asynchrony was found to exert the main influence accompanied by a small effect of prime duration. Experiment 3 (N=19; mean age 27.7) used a large range of priming onset asynchronies. We suggest to explain PLP by the Asynchronous Updating Model which relates it to the asynchrony of 2 central coding processes, preattentive coding of basic visual features and attentional orienting as a prerequisite for perceptual judgments and conscious perception. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: perceptual latency priming; temporal parameters; Asynchronous Updating Model; time course; stimulus onset asynchrony; visual masking; attention; Adult; Attention; Female; Humans; Male; Perceptual Masking; Reaction Time; Time Perception; Visual Perception; Attention; Priming; Stimulus Onset; Visual Masking; Visual Perception; Models; Time

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability

Leading, but not trailing, primes influence temporal order perception: Further evidence for an attentional account of perceptual latency priming. - Scharlau, Ingrid (Perception & Psychophysics)
Presenting a masked prime leading a target influences the perceived onset of the masking target. This priming effect is explained by the asynchronous updating model: The prime initiates attentional allocation toward its location, which renders a trailing target at the same place consciously available earlier. In 3 experiments, this perceptual latency priming by leading primes was examined jointly with the effects of trailing primes in order to compare the explanation of the asynchronous updating model with the onset-averaging and the P-center hypotheses. Exp 1 (n=15, mean age 27.1 yrs) showed that an attended, as well as an unattended, prime leads to perceptual latency priming. In addition, a large effect of trailing primes on the onset of a target was found. As Exp 2 (n=13, mean age 26.5 yrs) demonstrated, this effect is quite robust, although smaller than that of a leading prime. In Exp 3 (n=13, mean age 24.8 yrs), masked primes were used. Under these conditions, no influence of tra
Keywords: attention; leading primes; trailing primes; temporal order perception; perceptual latency priming; Adult; Attention; Female; Fixation; Ocular; Humans; Male; Perceptual Masking; Random Allocation; Time Perception; Visual Perception; Attention; Masking; Priming; Stimulus Frequency; Temporal Frequency; Temporal Order (Judgment)